2020
DOI: 10.1128/jvi.01957-19
|View full text |Cite
|
Sign up to set email alerts
|

Anterograde Viral Tracer Herpes Simplex Virus 1 Strain H129 Transports Primarily as Capsids in Cortical Neuron Axons

Abstract: The features of herpes simplex virus 1 (HSV-1) strain 129 (H129), including natural neurotropism and anterograde transneuronal trafficking, make it a potential tool for anterograde neural circuitry tracing. Recently anterograde polysynaptic and monosynaptic tracers were developed from H129 and have been applied for the identification of novel connections and functions of different neural circuitries. However, how H129 viral particles are transported in neurons, especially those of the central nervous system, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 63 publications
(86 reference statements)
1
13
0
Order By: Relevance
“…anterograde movements were 0.71 ± 0.43 and 0.75 ± 0.49 µm/s. This is close to 0.62 ± 0.18 µm/s of HSV anterograde movement in cortical neuron axons by the same statistical analysis method (Dong et al, 2020). However, The average of PRV movement speed was 1.2 µm/s in the research by Hogue et al (2018), while the events less than 0.5 µm/s were deleted in the data of Gaussian distribution.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…anterograde movements were 0.71 ± 0.43 and 0.75 ± 0.49 µm/s. This is close to 0.62 ± 0.18 µm/s of HSV anterograde movement in cortical neuron axons by the same statistical analysis method (Dong et al, 2020). However, The average of PRV movement speed was 1.2 µm/s in the research by Hogue et al (2018), while the events less than 0.5 µm/s were deleted in the data of Gaussian distribution.…”
Section: Discussionsupporting
confidence: 69%
“…However, The average of PRV movement speed was 1.2 µm/s in the research by Hogue et al (2018), while the events less than 0.5 µm/s were deleted in the data of Gaussian distribution. The velocity changed at different times post-infection (Dong et al, 2020). Moreover, the virus strain, the kind of neuron, and statistical analysis method may all affect the reported average speed of capsid transport in axon retrograde.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal mouse cortical neurons were isolated and cultured as described previously [25,26]. Briefly, the cerebral cortex was dissected from the forebrain of C57BL/6 mouse fetuses at embryonic day 18.5 (E18.5), and then dissociated with 0.25% trypsin (Gibco/Life Technologies)/DNase I (Sigma) for 15 min at 37 °C.…”
Section: Cells and Cell Culturementioning
confidence: 99%
“…The microfluidic plate has been introduced previously and was fabricated following the described protocol [10,26]. In brief, it contains two isolated chambers connected by multiple microchannels (700 μm long, 10 μm wide, and 3 μm deep), which allows only the axons to grow through but not the somas or dendrites.…”
Section: Microfluidic Assaymentioning
confidence: 99%
“…Different HSV-1 strains with different transmission properties, including F, 17, H129, and McIntyre-B, have been sequenced and compared for their transmission properties [ 106 ]. Dong et al recently showed that H129 capsid and envelope are transported in the axon separately, and notably, capsids are enveloped at axonal varicosity and terminals [ 107 ]. However, the detailed mechanism of HSV-1 transmission, especially why H129 gains the preferential anterograde transmission, remains unclear.…”
Section: Strategies For Optimizing and Developing Future H129-derimentioning
confidence: 99%